Communion Ecclesiologies as Contextual Theologies - Flanagan, Brian P. (Horizons, 2013)
This article argues that the predominance of communion language in ecclesiology in the past fifty years frequently functions as another instance of the universalization of a theological position rooted in a particular, dominant context—the fragmented, post-traditional world of the late twentieth-century West. First, it briefly discusses the concept of a contextual theology. It then traces three of the major contexts in which communion ecclesiology developed: the ecumenical movement and its desire for a new language of Christian unity, the Roman Catholic community's desire for language pointing to the spiritual/theological reality of the Christian church, and the broader cultural context of fragmentation and real or perceived disintegration of community found in late-modern Western societies. Finally, the article looks at some examples of ecclesiological reflection occurring outside of the dominant consensus of communion ecclesiology: the work of José Comblin in Latin America, and that of Elochukwu Uzukwu and other theologians of the church in African contexts.